First evidence of natural reproduction of the Allis shad Alosa alosa in the River Rhine following re‐introduction measures. Issue 2 (26th June 2015) - Hundt, M.; Scharbert, A.; Weibel, U.; Kuhn, G.; Metzner, K.; Jatteau, P.; Pies, A.; Schulz, R.; Gergs, R.
<x xml:space="preserve">Abstract</x> After stocking with larvae from the Gironde–Garonne–Dordogne population, in 2013, three young‐of‐the‐year Allis shad Alosa alosa, probably originating from natural reproduction, were documented for the first time in a period of nearly 100 years in the River Rhine. In 2014, a further increase was observed when 57 juveniles and eight adults were caught; seven of these eight adults were derived from stocking, indicating the success of stocking measures within the framework of the EU‐LIFE project.